A comparative analysis of ex ante credit spreads: structured finance versus straight debt finance - Pinto, João (2016)
Structured finance (SF) – project finance (PF) loans and asset securitization (AS) bonds – and straight debt finance (SDF) – corporate bonds (CB) – transactions are priced in segmented capital markets. Credit spreads are higher for PF loans than they are for AS and CB issues. SF and SDF credit spreads are directly related to default and currency risks, while the slope of the yield curve impacts negatively the credit spreads. The loan to value ratio proves positively related to PF loans and negatively related to AS bonds, while the number of banks has a negative impact on the credit spread for AS and CB issues. PF loan credit spreads and fees are shown to be complements rather than supplements. Borrowers from the U.K. raise funds in PF and CB markets at a higher credit spread and the impact of country risk on the credit spread is positive for PF and CB issues. The 2007/2008 financial crisis have imposed a significant impact on credit spreads. The average credit spread has increased 329.1 bps for PF loans, 206.5 bps for AS bonds, and 220.3 bps for CB issues during the crisis period. Finally, a robust hump-shaped relationship between credit spread and maturity is found for PF loans while a linear positive relationship remains strongly significant for CB.